Recent Advancement in BIPV Product Technologies: A Review - Akash Kumar, Shukla; Sudhakar, K.; Prashant, Baredar (Elsevier Ltd, 2017)
Application of building integrated photovoltaic (BIPV) technology in the building envelope gives an aesthetical and modern appearance. BIPV is a practical, innovative and promising technology for net zero emission buildings. This paper introduces the best in class of the BIPV products and their properties along with international guidelines and testing standards. BIPV products for rooftops, façades and windows have been highlighted in this paper. The properties of BIPV products incorporate solar PV efficiency, Voc, Isc, Pmax and fill factor (FF). The life cycle sustainable assessment of BIPV module has been reviewed by examining energy payback time and GHG emission.